The combination of the kaizen approach with the Design of Experiment (DoE) method for improving quality of the bread and donut products in SMEs - Wiyatno, Tri Ngudi; Kurnia, Hibarkah; Putri, Isria Miharti Maherni; Nugroho, Rifal (OPSI, 2024)
Competition for Small and Medium Enterprise (SME) products is currently getting tougher, in terms of quality, timely delivery, and competitive prices. SME customers of bread and donut products sometimes complain about the visual quality of bread and donut products that are stale, burnt, and dirty. The purpose of this research is to reduce product defects during the production process and improve the quality of the bread and donut products. This research method uses a Kaizen approach combined with the Design of Experiment (DoE) one-shoot case study method and uses organoleptic tests to assess the quality of bread and donut products. This study found that there were 3 product defect problems, namely bread and donut defects that did not rise, burnt donut defects, bread defects, and dirty donuts. This research resulted in a decrease in defects of 65% from 3.84% to 1.07%. While the best DoE test results used dough type C with 10 grams fermipan/yeast composition and 15 grams bread improver, stove 165-1750C, equipment cleaning frequency 1 time for each dough, and organoleptic test with 10% beetroot extract addition resulted in a color aspect score of 70 %, 65% aroma aspect, 68.5% texture aspect, and 70% taste aspect which is liked by many people.